2010
DOI: 10.1190/1.3503578
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent ocean bottom and vertical cable seismic acquisition for wavefield reconstruction

Abstract: In ocean-bottom seismic and vertical-cable surveying, receiver stations are stationary on the sea floor while a source vessel shoots on a predetermined [Formula: see text] grid on the sea surface. To reduce exploration cost, the shot point interval often is so coarse that the data recorded at a given receiver station are undersampled and thus irrecoverably aliased. However, when the pressure field and its [Formula: see text]- and [Formula: see text]-derivatives are measured in the water column, the nonaliased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is useful to compare this against the 'sinc interpolation formula' for pressure data only in eqn [11]. Based on the work by Robertsson et al (2008), Amundsen et al (2010) explored the benefits of interpolation of seabed node data where higher-order gradients of pressure data can also be measured, further constraining the interpolation problem and allowing for sparse sampling of the recorded wavefield. This difference in the two sinc interpolation formulas is fundamental and reflects the fact that the Nyquist sampling criterion has increased by a factor of 2 in eqn [13].…”
Section: Receiver-side Techniquesmentioning
confidence: 99%
“…It is useful to compare this against the 'sinc interpolation formula' for pressure data only in eqn [11]. Based on the work by Robertsson et al (2008), Amundsen et al (2010) explored the benefits of interpolation of seabed node data where higher-order gradients of pressure data can also be measured, further constraining the interpolation problem and allowing for sparse sampling of the recorded wavefield. This difference in the two sinc interpolation formulas is fundamental and reflects the fact that the Nyquist sampling criterion has increased by a factor of 2 in eqn [13].…”
Section: Receiver-side Techniquesmentioning
confidence: 99%
“…As pointed out by Robertsson et al (2008), signal theory implies that the crossline component of the pressure gradient measured by a multicomponent streamer (V y ) allows interpolation in the crossline direction of the seismic pressure in a spatial bandwidth that is up to twice the Nyquist wavenumber (Linden, 1959). More recently, Amundsen et al (2010) also showed how the same theory can be applied to ocean bottom node acquisition. Vassallo et al (2010) introduced multichannel interpolation by matching pursuit (MIMAP) as a technique to combine the information of the pressure and the crossline component of particle velocity to achieve crossline reconstruction.…”
Section: Introductionmentioning
confidence: 98%